An Overview of the Strengths and Challenges Related to Health on the First 10 Days after the Large Earthquake in the West of Iran, 2017 - Mahmoudreza PEYRAVI; Milad AHMADI MARZALEH; Amir KHORRAM-MANESH (Tehran University of Medical Sciences, 2019)
Background: The objective of the present study was to investigate the strength and weaknesses of healthcare management during the first 10 days after the earthquake in Sarpol-e Zahab in Kermanshah, Iran. Methods: This qualitative, observational study was conducted on November 13-23, 2017 in the disaster area, by using content analysis. Data was collected through experts and focus group interviews with professional and healthcare staff, and policy-makers. Results: Our findings were categorized into 7 major groups; environmental health; mental health; mothers, infants and children's health; field hospital; nutrition; contagious diseases; drug delivery. There were good cooperation and coordination regarding environmental health issues. However, other categories were handled by different organizations and resulted in a chaotic situation. Conclusion: The post-earthquake period is overwhelmed with considerable issues regarding the care of victims and therapeutic measures. Lack of quick, reliable, and appropriate management will result in extensive health issues, including epidemic, worsening of chronic diseases, and exacerbation of mental disorders.